Q: What is 5x2 - 3x 4x2 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

kjkjj

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

The first equality is: x2 - 5 = -4x2 which gives 5x2 - 5 = 0 which is equivalent to x2 - 5 = 0 The second equality is: -4x2 = 3x which gives 4x2 + 3x = 0 The two results are inconsistent.

for x = -2: x2 = 4, -5x2 = -20; 3x = -6 giving -20 - (-6) = - 20 + 6 = -14.

(x + 3)(3x^2 - 4x + 6)

Related questions

kjkjj

5x2y = 3x - 6y 5x2y + 6y = 3x y(5x2 + 6) = 3x y = (3x)/(5x2 + 6) This is a rational function.

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

The first equality is: x2 - 5 = -4x2 which gives 5x2 - 5 = 0 which is equivalent to x2 - 5 = 0 The second equality is: -4x2 = 3x which gives 4x2 + 3x = 0 The two results are inconsistent.

for x = -2: x2 = 4, -5x2 = -20; 3x = -6 giving -20 - (-6) = - 20 + 6 = -14.

3x4-7x3+5x2-3x+6

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

The answer is 37.

9. And the word is minus, not minis.

3(4x2 - x + 2)

y=4x2+3x+8

(x + 3)(3x^2 - 4x + 6)